2016
DOI: 10.1159/000451033
|View full text |Cite
|
Sign up to set email alerts
|

Designated Stroke Center Status and Hospital Characteristics as Predictors of In-Hospital Mortality among Hemorrhagic Stroke Patients in New York, 2008-2012

Abstract: Background: Although designated stroke centers (DSCs) improve the quality of care and clinical outcomes for ischemic stroke patients, less is known about the benefits of DSCs for patients with intracerebral hemorrhage (ICH) and subarachnoid hemorrhage (SAH). Hypothesis: Compared to non-DSCs, hospitals with the DSC status have lower in-hospital mortality rates for hemorrhagic stroke patients. We believed these effects would sustain over a period of time after adjusting for hospital-level characteristics, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…It has been shown that regardless of the individual predictors of in-hospital mortality, being admitted to a designated stroke center could improve survival after intracerebral hemorrhage. 3 The overall case-fatality proportion was 12.5% in current study. It reached up to 25.1% in Imam Reza University Hospital vs only 1.7% in Razi University Hospital.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…It has been shown that regardless of the individual predictors of in-hospital mortality, being admitted to a designated stroke center could improve survival after intracerebral hemorrhage. 3 The overall case-fatality proportion was 12.5% in current study. It reached up to 25.1% in Imam Reza University Hospital vs only 1.7% in Razi University Hospital.…”
Section: Discussionmentioning
confidence: 46%
“… 1 Hemorrhagic stroke ranks the highest with respect to in-hospital fatality among stroke subtypes, with a range of about 24%–28% reported based on various studies. 1 3 It is also considered a major public health problem with high morbidity and mortality in low- and middle-income countries, including Iran, with rates exceeding that in high-income countries. 4 8 …”
Section: Introductionmentioning
confidence: 99%
“…The effect of hospital characteristics and health systems of care—including physician expertise, case volumes, and care provision in dedicated neurocritical care units—on outcomes for patients with aSAH has been described in large nonrandomized studies. 67–69,71,75–77 Specifying exact case volumes for what should constitute a high-volume center versus a low-volume center is particularly challenging given the heterogeneity of studies. Thus, specific case numbers are not included in Recommendation 1; instead, the case numbers used in the 2012 aSAH guideline are included in the Synopsis for historical reference.…”
Section: Hospital Characteristics and Systems Of Carementioning
confidence: 99%
“…72,75 Stroke center designation has been associated with reduced in-hospital mortality for patients with aSAH. 71 Timely arrival of patients with aSAH in hospitals where they can receive both aneurysm treatment and neurocritical care is relevant given the risks for aneurysm rerupture and DCI. 70,73,74 According to US Nationwide Inpatient Samples, factors associated with treatment delay in aSAH were older age, non-White race, Medicaid payer status, surgical clipping, and admission to low-surgical-volume hospitals.…”
Section: Recommendations For Hospital Characteristics and Systems Of ...mentioning
confidence: 99%
“…Red blood cell count (RCC) 8 , mean corpuscular volume (MCV) 8 , mean platelet volume 9 , low diastolic blood pressure 10 during admission, pyrexia 10 , and severe obesity 11 were factors associated with post-stroke mortality in patients with ischemic stroke. In addition, anemia 12 and hospital size 13 influence post-stroke mortality in patients with hemorrhagic stroke. Moreover, white blood cell count 14 , serum creatinine levels 14 , hyperglycemia 15 , hyponatremia 16 , red cell distribution width (RDW) 17 , systolic blood pressure 14 , hyperthermia 18 , and residential environment 19 influence post-stroke mortality in patients with combined ischemic and hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%